Analysis Management Strategy In Development Batik As Lampung In Batik Elfira Collection Lampung South - Rachmad Ryo Ryanda Subing; Ni Putu Widhia Rahayu (Cita konsultindo, 2024)
Batik Elfira Collection Lampung South own problem that is production batik Still based on P.O. Material raw material Still depends on supply outside province Lampung, because there are no shops that sell the main raw material for batik, especially wax (wax). batik), batik dyes, and batik equipment. This may be due to a lack of specifically management strategy Which done. Objective from study This is For analyze strategy business Which appropriate on Batik Elfira Collection Lampung South And improving income at the Batik Elfira Collection South Lampung. The data source is questionnaires and interviews. The data collection method is primary data which is carried out using method observation, And questionnaire. Results study This showing that based on diagram The SWOT Matrix above is known as Batik Elfira Collection South Lampung is in the first quadrant, where the situation of external and internal factors is positive which means that the environment faced the opportunity is relatively greater than the threat, while the strength is relatively greater superior compared to its weaknesses. The strategy that must be applied in this condition is supports aggressive growth policies ( growth oriented strategy ) which refers to In the industrial world there are market leaders and the next in line are called market challengers Challenger).